The Effect of Shotblocker Use on Pain Scores in Infants Undergoing Intramuscular Immunization at Jatinangor Primary Health Center - Syahla Jahda Syahidah; Ida Widiawati; Santi Sofiyanti; Rika Resmana (Universitas Muhammadiyah Semarang, 2026)
Pain caused by immunization procedures often leads to anxiety, fear, and even trauma in children, potentially affecting their adherence to the immunization schedule. Shotblocker is a simple device based on the Gate Control Theory, which reduces pain perception through tactile stimulation. This study aimed to determine the effect of Shotblocker use on pain scores among two-month-old infants receiving intramuscular immunization. A quasi-experimental design with a posttest-only control group was employed on 80 infants, divided into an intervention group (with Shotblocker) and a control group (without Shotblocker). Pain was assessed using the FLACC scale. The results showed that the mean pain score in the intervention group was 3.57 (SD = 0.879), while in the control group it was 6.48 (SD = 0.727). An independent sample t-test indicated a significant difference between the groups (p < 0.05). These findings demonstrate that Shotblocker significantly reduces pain intensity in infants following intramuscular immunization. Shotblocker may serve as a safe and effective non-pharmacological tool to improve pediatric comfort.